Does paddling in canoes cause asymmetry of muscle mass and fat mass in high level athletes? = Czy wiosłowanie w kanadyjce powoduje asymetrię rozkładu masy mięśniowej i tłuszczu? - Rynkiewicz, Mateusz; Baumgarten, Maciej; Mroczkowski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This work aims to investigate whether long-term canoeing causes asymmetry of muscle and fat distribution. It was assumed that long-term paddling would be reflected in the asymmetry of segmental body composition analysis. The research involved 40 competitors who train canoeing, among whom, 19 have the experience of 7 years minimum, and 21 of no longer than 3 years. The measurement of electrical bioimpedance was used as the research method, which allowed the authors to determine muscle mass and fat mass in the upper and lower limbs, and the torso. The asymmetry indicators were calculated and then the significance tests on differences between both groups were used.
Keywords: asymetria; masa mięśniowa; kajakarstwo; trening sportowy; asymmetry; muscle mass; canoeing; sports training